Protótipo para análise de viscosidade em óleo lubrificante - Schwab, Bruna Camila (2023)
In the lubrication field, the property known as viscosity is of utmost importance for selecting suitable lubricating oils based on their application. Thus, this present study aims to develop a prototype for viscosity analysis in lubricating oils, intended to provide support for the studies of students at the Federal Technological University of Paraná (UTFPR) in Guarapuava. The proposed device adopts a rotating model of parallel plates, manufactured through the 3D printing technique. The determination of viscosity is carried out through an equation that integrates variables measured by a dynamometer, encoder, and Arduino.To validate the results obtained by the device, tests were conducted on a commercial rheometer using multi-viscosity and mono viscosity oils such as 5W30, 15W40, 20W50, SAE 68, and SAE 90. These tests involve a comparison between the results of the prototype and the commercial rheometer. The comparison revealed that the prototype is capable of differentiating the viscous characteristics in the tested oils. Therefore, it can be employed in analytical and comparative studies for viscosity analysis in lubricating oils.